Determination of glycosylation degree for glycoconjugate vaccines using a solid‐phase extraction combined with liquid chromatography and tandem mass spectrometry method. Issue 14 (8th June 2020) - Long, Zhen; Li, Maoguang; Dahl, Jeffrey; Guo, Zhimou; Li, Yanan; Hao, Hongyuan; Li, Yueqi; Li, Changkun; Mao, Qiqi; Huang, Taohong
Abstract: In this study, a solid‐phase extraction with liquid chromatography and tandem mass spectrometry method was developed to determine the degree of glycosylation of glycosylation sites and the ratio of free carrier protein to total carrier protein for glycoconjugate vaccines. To remove and enrich the glycosylated peptides, a solid‐phase extraction method was developed, optimized, and hyphenated to liquid chromatography−tandem mass spectrometry. The developed solid‐phase extraction with liquid chromatography−tandem mass spectrometry method was shown to possess a wide linear dynamic range (0.03−100 μg/mL), a high sensitivity (0.03 μg/mL for CRM197), good interday and intra‐day precision (relative standard deviation of peak area < 3.3%), and good recoveries from vaccine matrix (90−105%). Finally, the method was utilized to determine the degree of glycosylation and free carrier protein to total carrier protein ratio for pneumococcal conjugate vaccines and meningococcal vaccines. For quality evaluation of glycoconjugate vaccines, the method could provide more information than the traditional size exclusion chromatography method. Fourteen and twelve reported glycosylation sites for CRM197‐ and tetanus toxin‐based vaccines can be detected, respectively.